Percutaneous transluminal angioplasty (PTA) of the iliac and femoral arteries - Tiscornia, Eduardo; di Trápani, Nelson (Cirugía del Uruguay, 1991)
Percutaneous transluminal angioplasty (Doter mehod) was initial/y rjected by he majoiy of agiologss and vascular surgeons. With the introduction of the inextensible Grunzig bal/oon caheter there apeared a genral acceptance of the method but cerain doubts remain on is indications and lonrterm resuhs. The auhors rt on their 7 year long exeience on angiolasy treatment of iliac and femoal oclusive disease. 4 aiens were ol/owed up for a peiod of 1 to 5 yeas, in odr to get to know PT A efciveness